Interleukin-5 Expression in the Lung Epithelium of Transgenic Mice Leads to Pulmonary Changes Pathognomonic of Asthma - Lee, James J. (The Rockefeller University Press, 1997)
We have generated transgenic mice that constitutively express murine interleukin (IL)-5 in the lung epithelium. Airway expression of this cytokine resulted in a dramatic accumulation of peribronchial eosinophils and striking pathologic changes including the expansion of bronchusassociated lymphoid tissue (BALT), goblet cell hyperplasia, epithelial hypertrophy, and focal collagen deposition. These changes were also accompanied by eosinophil infiltration of the airway lumen. In addition, transgenic animals displayed airway hyperresponsiveness to methacholine in the absence of aerosolized antigen challenge. These findings demonstrate that lung-specific IL-5 expression can induce pathologic changes characteristic of asthma and may provide useful models to evaluate the efficacy of potential respiratory disease therapies or pharmaceuticals.